2020
DOI: 10.1123/ijspp.2019-0464
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Thermoregulation and Performance via Mild Dehydration in Ice Hockey Goaltenders

Abstract: During play, ice hockey goaltenders routinely dehydrate through sweating and lose ≥2% body mass, which may impair thermoregulation and performance. Purpose: This randomized, crossover study examined the effects of mild dehydration on goaltender on-ice thermoregulation, heart rate, fatigue, and performance. Methods: Eleven goaltenders played a 70-minute scrimmage followed by a shootout and drills to analyze reaction time and movements. On ice, they either consumed no fluid (NF) and lost 2.4% (0.3%) body mass or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Despite greater external loads with CHO MR, internal loads were not different between conditions. The absence of diverging RPE values between CHO and PLA MR with the development of physical fatigue opposes previous CHO-ingestion ice-hockey research (15)(16)(17). However, this observation has been frequently repeated in existing CHO MR exercise research (18)(19)(20).…”
Section: Overtimementioning
confidence: 88%
See 3 more Smart Citations
“…Despite greater external loads with CHO MR, internal loads were not different between conditions. The absence of diverging RPE values between CHO and PLA MR with the development of physical fatigue opposes previous CHO-ingestion ice-hockey research (15)(16)(17). However, this observation has been frequently repeated in existing CHO MR exercise research (18)(19)(20).…”
Section: Overtimementioning
confidence: 88%
“…Alternatively, Lignell's group examined 3-on-3 full-ice competition, but only during an OT period ( 5 ). The present protocol has previously been used in other hockey research, but for analyzing goaltender performance ( 17 ). Therefore, the current analysis of player external and internal loads across time in small-sided 3-on-3 hockey scrimmage is novel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement, when both sexes experienced a similar magnitude of dehydration ($1.2%-1.8% body mass loss greater than control), only females experienced a higher T c ($0.3 C) during intermittent exercise (12-14, 18, 19). Thus, an inability to adequately maintain a thermoneutral T c appears to be initiated at $0.5%-1.0% body mass loss in females (12,16,18), whereas literature concerning male subjects reported that the physiological consequences of exercise-induced mild dehydration were present only beyond >1% body mass loss (20,21). Though limited, these data suggest that thermoregulatory capacity may be impaired at lower relative magnitudes of exercise-induced dehydration in females compared with males, and this hypothesis warrants direct examination in future studies.…”
Section: Thermoregulatory and Cardiac Responses To Exercise-induced Dehydrationmentioning
confidence: 99%